Liability for negligent misstatement inducing a contract in South Africa and Germany - von Auer, B I (Department of Commercial Law, 2023)
The law in the area of negligent misrepresentation has undergone major changes during this century, in the legal systems of both South Africa and Germany. Which remedies does one have if financial loss is caused because another made a false statement. The legal system in South Africa stands in the tradition of Roman, Roman-- Dutch and English law, while Germany derived its civil law from Roman principles. Neither of these historical legal backgrounds provided a complete answer to the question posed above, and if there were answers, they have been subjected to many changes and uncertainties due to the growing complexity of cases. The complexity is increased by the fact that misrepresentation overlaps both the law of contract as well as delict and this challenges the distinction between the two of them. Through the development of given legal principles, it is now an established rule in South · African and German law that an action exists for the recovery of damages which were caused by negligent misrepresentation in the pre-contractual sphere. The object of this dissertation is to depict the development of this remedy and to compare the adequacy and precedence of the existing rule in South Africa and Germany.